2015
DOI: 10.1093/biosci/biv018
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ocean Management: Identifying the Critical Ingredients of Dynamic Approaches to Ocean Resource Management

Abstract: Dynamic ocean management, or management that uses near real-time data to guide the spatial distribution of commercial activities, is an emerging approach to balance ocean resource use and conservation. Employing a wide range of data types, dynamic ocean management can be used to meet multiple objectives-for example, managing target quota, bycatch reduction, and reducing interactions with species of conservation concern. Here, we present several prominent examples of dynamic ocean management that highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
197
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 212 publications
(199 citation statements)
references
References 82 publications
2
197
0
Order By: Relevance
“…Given the dynamic climate and oceanographic variability of the CCS and the profound impact of this variability on marine resources, there is momentum building to move toward fisheries management strategies that incorporate real-time and forecasted environmental information to inform the temporal and spatial extent of fishery closures (Hobday et al 2013;Lewison et al 2015;Maxwell et al 2015). For example, to predict the spatiotemporal overlap between protected and targeted species, empirical statistical relationships are used to link marine species to their preferred environment, and then predict the distribution of those species based on more widely available oceanographic observations or predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Given the dynamic climate and oceanographic variability of the CCS and the profound impact of this variability on marine resources, there is momentum building to move toward fisheries management strategies that incorporate real-time and forecasted environmental information to inform the temporal and spatial extent of fishery closures (Hobday et al 2013;Lewison et al 2015;Maxwell et al 2015). For example, to predict the spatiotemporal overlap between protected and targeted species, empirical statistical relationships are used to link marine species to their preferred environment, and then predict the distribution of those species based on more widely available oceanographic observations or predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Although these tools allow for operational implementation of DOM, there is a larger question of how DOM fits within current fisheries management regimes. Previous studies have shown that DOM does not seek to supplant existing adaptive management processes but falls within the implementation component of that framework (7,8). For example, move-on rules as they are currently implemented in numerous fisheries do not occur at a predetermined time or location and do not require management council review for each application of the measure (5, 10); rather, the distance which fishermen must move following a bycatch event is determined during the council review process and the move-on rule is applied in near real time on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing static and dynamic measures are lacking despite the potential to increase efficiency through the use of dynamic measures to align the scales of resource variability, resource use, and resource management (7,8). In a precursor to the recent work on dynamic management, Grantham et al (42) looked at the efficiency of closures to reduce bycatch by examining permanent full-fishery closures, seasonal full-fishery closures, and a series of temporary (monthly) time-area closures.…”
Section: Evaluation Of Static Vs Dynamic Management Measuresmentioning
confidence: 99%
See 2 more Smart Citations